Gene expression of biopsied murine preimplantation embryos / Norhazlin Jusoh @ Mohd Yusoff - Jusoh @ Mohd Yusoff, Norhazlin (2015)
Biopsy of embryo is a prerequisite technique employed in Preimplantation Genetic Diagnosis (PGD). Removal of one or two intact blastomeres can be carried out without detriment to embryonic development. However, the effect of piezo-assisted biopsy on gene expression of embryos remains to be elucidated. This study was conducted to elucidate the effect of piezo-assisted biopsy on the 8-cell, morula and blastocyst stages on embryonic development, global gene expression and their functional pathways. Following zona breaching by piezo-drilling, single blastomeres were removed from in vz'vo-derived 8-cell ICR mouse embryos. Biopsied embryos were allowed to develop further in Ml6 medium, and collected for RNA extraction after 1 h (8-cell), 16 h (morula) and 42 h (blastocyst). cDNA were converted, amplified, labelled and hybridized on the GeneChip®. Microarray data were analysed using GeneSpring GX 12. Gene expression of non-biopsied and post-biopsied embryos at the 8-cell, morula and blastocyst stages were compared using the t-test with p<0.05, including fold change of >1.5 for each gene. Results showed a significant difference in blastocyst development after piezo-assisted biopsy. A total of 82 genes, 75 genes and 66 genes were significantly different at the 8-cell, morula and blastocyst stages respectively. The differentially expressed genes were annotated using DAVID software for Gene Ontology and GO Metacore for pathways analyses. Several enriched genes at each stage were validated using RT-qPCR. The enriched pathways involved were energy metabolism, cell cycle, immune response and fatty acid metabolism. Elucidation of these changes provides a greater understanding of molecular alterations after piezo-assisted biopsy.